2022
DOI: 10.1002/smll.202200277
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Bouncing: Fundamentals, Regulations, and Applications

Abstract: Droplet impact is a ubiquitous phenomenon in nature, daily life, and industrial processes. It is thus crucial to tune the impact outcomes for various applications. As a special outcome of droplet impact, the bouncing of droplets keeps the form of the droplets after the impact and minimizes the energy loss during the impact, being beneficial in many applications. A unified understanding of droplet bouncing is in high demand for effective development of new techniques to serve applications. This review shows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 249 publications
(388 reference statements)
1
28
0
Order By: Relevance
“… 53 In these cases, by increasing the droplet diameter, the Ohnesorge number, i.e., the ratio of viscous forces to the inertia and surface tension forces, decreases and enhances the bouncing dynamics. 31 , 54 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 53 In these cases, by increasing the droplet diameter, the Ohnesorge number, i.e., the ratio of viscous forces to the inertia and surface tension forces, decreases and enhances the bouncing dynamics. 31 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…53 In these cases, by increasing the droplet diameter, the Ohnesorge number, i.e., the ratio of viscous forces to the inertia and surface tension forces, decreases and enhances the bouncing dynamics. 31,54 Energy Cycle. The droplet bouncing process involves multiple energy conversion cycles, as shown in Figure 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that rougher macrostructures make the surface more hydrophilic, and the micro-/nanostructures produce the reverse consequences. 38 In this way, E. indica leaf surface seems more hydrophilic than E. crusgalli and S. viridis, while it is also affected by the chemical compositions of the leaves. Besides, some long prickles distribute sparsely on the surface (Figure 1C 4 ).…”
Section: Measurement Of Surface Tension and Adhesivementioning
confidence: 98%
“…The impingement of the compound drop, such as Janus, core-shell, and particle-laden configurations, can bring more opportunities for applications owing to their particularities and numerous combinations of complex drops and complex surfaces [7,8]. Extensive studies have been carried out to investigate the mechanisms of the drop bouncing and the methods for bouncing promotion or suppression [9,10]. The drop dynamics can be governed by the theoretical Rayleigh limit given by…”
Section: Introductionmentioning
confidence: 99%